A novel ratiometric fluorescent probe for the detection of hydrogen peroxide in human gastric carcinoma HGC-27 cells. Issue 12 (17th March 2020) - Xie, Yong; Chen, Zhu; Hu, Linan; Zhang, Hailiang; Xu, Pengfei; Pan, Ke
Abstract : In this work, we report a new fluorescent probe JNH-1 for the ratiometric detection of H2 O2 . Abstract : Hydrogen peroxide (H2 O2 ) has been recognized as one of the most significant ROS in human health and disease. In this work, we report a new fluorescent probe JNH-1 for the ratiometric detection of H2 O2 . The probe JNH-1 showed a highly selective fluorescent response to H2 O2 against other interferences of ROS and RNS. In addition, this probe was successfully applied for the monitoring and imaging of H2 O2 in living human gastric carcinoma HGC-27 cells.